Alcoholismo y rendimiento académico en los alumnos de los colegios de la región suoriente del cantón Loja - Vargas Mendoza, Cristian Daniel (2014)
This paper called: ALCOHOL AND ACADEMIC PERFORMANCE OF STUDENTS IN COLLEGE REGION SOUTH EAST CANTON Loja ; its main objective : To determine the relationship between alcoholism and academic achievement in students from schools in the southeastern region of Loja canton during the period March - August 2013. The investigation of analytical , observational and transversal was conducted at the Technical College Manuel José Rodríguez ( Malacatos ) , Joint Vilcabamba ( Vilcabamba ) National College and the Benjamin School Carrión ( Yangana ) in the above period , with the following specific objectives as determine the number of students who consume alcohol, identify gender and age when he started drinking , identify the causes and in the company of a drinking occurs, determine how often alcohol is consumed, identify which sometimes Alcohol is consumed and whether alcohol affects and how it does in their academic performance , he polled 530 students between women and men the same who met all inclusion criteria . The following results than 290 students that corresponds to a 54.72 % consume alcohol, of which 22.07 % had a lower average 7 ( FAILED ) and a 17.24 % average between 8.51- 9, the predominant genus in consumption is 52.76% male with a 38.62 % started drinking between 16 to 17 years, the most frequent cause for which acceptance is consumed with 43.10% , and they do in the company of fellow college with a 52.07 % a 51.72 % consumed at least once a month and perform at parties with 51.04% , their academic performance has been maintained over time coming consuming alcohol in a 61.72 %. Keywords: Alcohol, Alcoholism, Academic Achievement.